2021
DOI: 10.3389/fonc.2021.772671
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC11 Promotes Hepatocellular Carcinoma Progression via Upregulation of UBE2T in a m6A-Dependent Manner

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent malignancies and the third leading cause of cancer-related deaths worldwide. Besides, it has been revealed that long non-coding RNA (LncRNA) cancer susceptibility candidate 11 (CASC11) is involved in cancer progression. However, the functional role and underlying mechanism of CASC11 in HCC remains largely unknown. In this context, here, it was found that CASC11 was upregulated in HCC tissues and associated with tumor grades, metastasis, and prognosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The two mechanisms underlying this process of tumor development involve the ubiquitin-conjugating enzyme E2T (UBE2T) and an m6A reader protein YT521-B homology domain family 2 (YTHDF2), respectively. CASC11 lowers the m6A level of UBE2T and thus stabilizes it by recruiting an increased amount of human AlkB homolog H5 (Chen et al, 2021). The RNA METTL16, similar to METTL3, serves as a link between m6A modification and the development of HCC.…”
Section: Non-coding Rnas Suppress the Progression Of Hepatitis B Viru...mentioning
confidence: 99%
“…The two mechanisms underlying this process of tumor development involve the ubiquitin-conjugating enzyme E2T (UBE2T) and an m6A reader protein YT521-B homology domain family 2 (YTHDF2), respectively. CASC11 lowers the m6A level of UBE2T and thus stabilizes it by recruiting an increased amount of human AlkB homolog H5 (Chen et al, 2021). The RNA METTL16, similar to METTL3, serves as a link between m6A modification and the development of HCC.…”
Section: Non-coding Rnas Suppress the Progression Of Hepatitis B Viru...mentioning
confidence: 99%
“…In laryngeal squamous cell carcinoma (LSCC), increased expression of ALKBH5 can promote tumorigenesis in an m 6 A‐YTHDF2‐dependent manner by promoting the lncRNA KCNQ1OT1‐HOXA9 signaling axis [ 281 ]. In HCC, the lncRNA CASC11 is upregulated and associated with poor survival and metastasis [ 282 ]. CASC11 stabilizes UBE2T mRNA by recruiting ALKBH5 m 6 A activity and also by inhibiting UBE2T mRNA association with YTHDF2 [ 282 ].…”
Section: Molecular Alterations In Cancer Metastasismentioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2 T (UBE2T, also known as E2 ubiquitin-conjugating enzyme T, FANCT, PIG50 and HSPC150) belongs to the UBE2 superfamily, which plays a fundamental role in the second step of ubiquitination. Following previous studies that reported that UBE2T was involved in the regulation of DNA repair in Fanconi anaemia (FA), it was recently molecularly identified as a risk factor closely associated with oncogenesis, metastasis, survival and prognosis in human patients or mammal animals with cancer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%